Third Year Hon. Mention: Media Coverage of The Billionaire Space Race: The Case of the Canadian Broadcasting Corporation and Democracy Now! WRIT 3011, Reading the News.CD: Karen Ruddy. - Fetila, Mihnea (Noteworthy: The LA&PS Writing Prizes, 2022)
“Billionaire Space Race” lays bare media bias in a thorough and well-evidenced analysis of the news coverage. It fulfills the requirements of the assignment beautifully, offering a clear contrast and plenty of support for its claims. The writer of this well-researched and convincing paper carefully employs a variety of critical lenses while analyzing both the CBC’s and Democracy Now’s media coverage of Jeff Bezos and Richard Branson’s recent extra-terrestrial exploits. The paper is written in fluent academic style and its composer makes excellent use of media theory to explore the tone, framing, and visuals behind both networks’ reporting on the two vanity projects. The author has done particularly well to pack so much cogent and telling analysis into only a few pages—no space is wasted and no stone left unturned either.